INVENTARISASI ASSET KETAHANAN SOSIAL DI DESA RATTE KABUPATEN POLEWALI MANDAR DENGAN PENDEKATAN ASSET BASED COMMUNITY DEVELOPMENT - Hildayanti, Andi; Machrizzandi, M Sya’rani; Tajuddin, Muhammad (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2023)
Ratte Village, which is located in Tutar or Tubbi Taramanu District, is one of the underdeveloped villages in Polewali Mandar Regency, West Sulawesi Province. The Village Building Index Index shows the lowest index. This is what underlies the implementation of this research activity to be carried out in Ratte Village seeing the status of the underdeveloped village. Through this Asset-Based Community Development approach in a sustainable manner, it can establish community independence by increasing income to increase welfare. This study aims to inventory Social Security Assets in Ratte Village, Polewali Mandar Regency with the Asset Based Community Development (ABCD) Approach. This research uses action research or Participatory Action Research which is carried out through stages (1) Discovery (Assessment); (2) Dream (Dream); (3) Design (procedure); and (4) Define and Destiny. The results of the study indicate that the potential or ability of cooperation, social networks, and social harmony, as well as the activeness of several correctional institutions that are intertwined among the people of Ratte Village are quite strong. Among the 4 (four) social indicators in the IDM, it is known that the education indicator is the indicator with the highest index of achievement. This is reflected in the very high motivation to learn and public awareness in the field of education. The availability of educational facilities and mountain water resources as a mode of driving the village electricity network is also sufficient to help the community carry out daily activities.